2023
DOI: 10.3389/fimmu.2023.1146077
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional control of ILC identity

Abstract: Innate lymphoid cells (ILCs) are heterogeneous innate immune cells which participate in host defense, mucosal repair and immunopathology by producing effector cytokines similarly to their adaptive immune cell counterparts. The development of ILC1, 2, and 3 subsets is controlled by core transcription factors: T-bet, GATA3, and RORγt, respectively. ILCs can undergo plasticity and transdifferentiate to other ILC subsets in response to invading pathogens and changes in local tissue environment. Accumulating eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 168 publications
0
7
0
Order By: Relevance
“…C1 was characterized by a gene expression profile found in both ILC2s (CCR9, CD24a) (48,49) and ILC3s (Il22, Klrb1b) (50, 51) (Fig. 3E), a transcriptional signature in line with observed plasticity among ILC populations (52). C5 was defined by an activated ILC2 gene signature (Gata3, Klrg1, Il5, Il13, Il1rl1) (20, 53) (Fig.…”
Section: Prenatal Inflammation Transcriptionally Enhances Lung Ilc2 H...mentioning
confidence: 81%
“…C1 was characterized by a gene expression profile found in both ILC2s (CCR9, CD24a) (48,49) and ILC3s (Il22, Klrb1b) (50, 51) (Fig. 3E), a transcriptional signature in line with observed plasticity among ILC populations (52). C5 was defined by an activated ILC2 gene signature (Gata3, Klrg1, Il5, Il13, Il1rl1) (20, 53) (Fig.…”
Section: Prenatal Inflammation Transcriptionally Enhances Lung Ilc2 H...mentioning
confidence: 81%
“…Additionally, we obtained 292 genes associated with innate lymphoid cells from DisGeNet. Moreover, our analysis of additional studies revealed that BCL11B, BATF, RUNX3, and ZBTB46 are associated with lymphoid cell immune typing ( Korchagina et al, 2023 ).…”
Section: Methodsmentioning
confidence: 88%
“…ILCs lack specific antigen-specific receptors like T cell receptors (TCRs) or B cell receptors (BCRs), leading to their ability to respond quickly to stimuli, particularly cytokines. ILCs can be classified into three distinct functional groups, namely ILC1s, ILC2s, and ILC3, similar to the classification of CD4 + T cells, with each corresponding to Th1, Th2, and Th17 cells, respectively [ 125 ].…”
Section: Immunological Barriers By Innate Lymphoid Cellsmentioning
confidence: 99%